Experiences in Tick Control by Acaricide in the Traditional Cattle Sector in Zambia and Burkina Faso: Possible Environmental and Public Health Implications - De Meneghi, Daniele; Stachurski, Frédéric; Adakal, Hassane (Frontiers in Public Health, 2016)
Livestock, especially cattle, play a paramount role in agriculture production systems, particularly in poor countries throughout the world. Ticks and tick-borne diseases (TBDs) have an important impact on livestock and agriculture production in sub-Saharan Africa. The authors review the most common methods used for the control of ticks and TBDs. Special emphasis is given to the direct application of acaricides to the host animals. The possible environmental and public health adverse effects (i.e., risks for the workers, residues in the environment and in food products of animal origin) are mentioned. The authors present two case studies, describing different field experiences in controlling ticks in two African countries. In Zambia (Southern Africa), a strategic dipping regime was used to control Rhipicephalus appendiculatus ticks, vectors of theileriosis, a deadly disease affecting cattle in the traditional livestock sector in Southern Province. The dipping regime adopted allowed to reduce the tick challenge and cattle mortally rate and, at the same time, to employ less acaricide as compared to the intensive dipping used so far, without disrupting the building-up of enzootic stability. In Burkina Faso (West Africa), where dipping was never used for tick control, an acaricide footbath was employed as an alternative method to the traditional technique used locally (portable manual sprayers). This was developed from field observations on the invasion/attachment process of the Amblyomma variegatum ticks – vector of cowdriosis – on the animal hosts, leading to a control method aimed to kill ticks temporarily attached to the interdigital areas before their permanent attachment to the predilection sites. This innovative method has been overall accepted by the local farmers. It has the advantage of greatly reducing costs of treatments and has a minimal environmental impact, making footbath a sustainable and replicable method, adoptable also in other West African countries. Although the two methods described, developed in very different contexts, are not comparable – if public health and environmental implications are taken into account, if a balance among efficacy of the control method(s), cost-effectiveness and sustainability is reached – a way forward for the implementation of a One Health strategy can be set.